2010
DOI: 10.1128/jvi.00209-10
|View full text |Cite
|
Sign up to set email alerts
|

Vif of Feline Immunodeficiency Virus from Domestic Cats Protects against APOBEC3 Restriction Factors from Many Felids

Abstract: To get more insight into the role of APOBEC3 (A3) cytidine deaminases in the species-specific restriction of feline immunodeficiency virus (FIV) of the domestic cat, we tested the A3 proteins present in big cats (puma, lion, tiger, and lynx). These A3 proteins were analyzed for expression and sensitivity to the Vif protein of FIV. While A3Z3s and A3Z2-Z3s inhibited ⌬vif FIV, felid A3Z2s did not show any antiviral activity against ⌬vif FIV or wild-type (wt) FIV. All felid A3Z3s and A3Z2-Z3s were sensitive to Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(122 citation statements)
references
References 58 publications
7
115
0
Order By: Relevance
“…The CBF-␤ gene sequence was submitted to GenBank under accession number KM250107. (49,52). To test if feline CBF-␤ interacts with FIV Vif, we first cloned the CBF-␤ gene from a Chinese domestic cat.…”
Section: Cbf-␤-kd 293t Cell Generationmentioning
confidence: 99%
“…The CBF-␤ gene sequence was submitted to GenBank under accession number KM250107. (49,52). To test if feline CBF-␤ interacts with FIV Vif, we first cloned the CBF-␤ gene from a Chinese domestic cat.…”
Section: Cbf-␤-kd 293t Cell Generationmentioning
confidence: 99%
“…These restriction factors are incorporated into the progeny virions and enzymically convert viral cDNA cytosines to uracils during reverse transcription, which can debilitate viral function (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013). Although original studies focused on human APOBEC3G (Harris et al, 2003;Mariani et al, 2003;Sheehy et al, 2002;Zhang et al, 2003), subsequent work revealed that all placental mammals have APOBEC3 enzymes (Münk et al, 2012), albeit different numbers, and that these enzymes have the potential to attenuate the infectivity of a broad spectrum of viruses, including simian immunodeficiency virus (SIV) (Mariani et al, 2003), feline immunodeficiency virus (FIV) (Münk et al, 2008;Zielonka et al, 2010), bovine immunodeficiency virus (BIV) (LaRue et al, 2010) and small ruminant lentiviruses (SRLVs; e.g. Maedi-Visna virus and caprine arthritis encephalitis virus) (LaRue et al, 2010).…”
mentioning
confidence: 99%
“…It is known that domestic cat (F. catus) expresses five kinds of APOBEC3 proteins, APOBEC3Z2a, APOBEC3Z2b, APOBEC3Z2c, APOBEC3Z3 and APOBEC3Z2Z3 (LaRue et al, 2010;Münk et al, 2008;Stern et al, 2010;Zielonka et al, 2010), and that feline APOBECZ3 and APOBEC3Z2Z3 have the ability to restrict FIV infectivity (Zielonka & Münk, 2011). To determine whether CBF-b was required for FIV Vif as a co-factor to degrade feline APOBEC3s, we constructed a FLAG-tagged FIV Vif expression plasmid as follows: the codon-optimized ORF of FIV strain Petaluma with a FLAG-tag at the C terminus (the sequence is available upon request) was obtained from GeneArt Gene Synthesis service (Life Technologies).…”
mentioning
confidence: 99%
“…It is currently unknown whether genetic adaptation to the new host occurs, for instance, in genes that are at the forefront of hostpathogen interactions (10,11). Here, host-encoded antiviral restriction factors like APOBEC3 cytidine deaminases and the viral proteins counteracting this restriction, like the lentiviral Vif and the FV Bet proteins, are prominent examples for rapid coevolution and cospeciation (12,13,14,15).…”
mentioning
confidence: 99%